Faktor- Faktor yang Mempengaruhi Devidend Payout Ratio pada Perusahaan Property dan Real Estate - Satryo Wibowo; Yupiter Gulo; Mariane Ellen Harmoni Purbojati (The Indonesia Capital Market Institute, 2019)
The purpose of this research is to test and analyze empirically the influence of return on investment, return on equity, net profit margin, debt to equity ratio, and earnings per share toward stock price. This research also to compare and improve the results of previous studies. The objects used in this study is property, real estate, and building construction industry sector listed on the Indonesia Stock Exchange (IDX) for six years 2011-2016. The purposive sampling is used as sampling technique to obtain 11 companies listed in property, real estate, and building construction that met the criteria and were analyzed using descriptive statistics and panel data regression with fixed effect model to test the hypotheses. This research is processed using E-views 9 software. The results of the research as follows, return on investment, return on equity, net profit margin, and earnings per share influence stock price. While debt to equity ratio do not influence stock price. The purpose of this research is to test and analyze empirically the influence of current ratio, debt to equity ratio, return on asset, firm size, and growth toward dividend payout ratio. This research also to compare and improve the results of previous studies. The objects used in this study is property and real estatecompanies that listed in the Indonesia Stock Exchange (IDX) for five years 2012-2016. The purposive sampling is used as sampling technique to obtain 7 companies listed in property and real estate that met the criteria and were analyzed using descriptive statistics and multiple linear regression to test the hypothesis. This research is processed using E-views 9 software. The results of the research as follows, current ratio, return on asset, and firm size influence dividend payout ratio. While debt to equity ratio and growth do not influence dividend payout ratio.